2022
DOI: 10.1038/s41467-022-29679-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting extracellular and intracellular distribution of nanoparticles and their contribution to therapeutic response by monochromatic ratiometric imaging

Abstract: Efficient delivery of payload to intracellular targets has been identified as the central principle for nanomedicine development, while the extracellular targets are equally important for cancer treatment. Notably, the contribution of extracellularly distributed nanoparticles to therapeutic outcome is far from being understood. Herein, we develop a pH/light dual-responsive monochromatic ratiometric imaging nanoparticle (MRIN), which functions through sequentially lighting up the intracellular and extracellular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Moreover, a previous report has revealed that the nanoparticles that arrived at the tumor sites could be partially internalized by various cell components. 45 As a result, the red fluorescence signals in tumors could be attributed to the fluorescence dyes that were encapsulated in and released from the nanovehicles, which could be used to characterize their distribution profiles in tumor tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a previous report has revealed that the nanoparticles that arrived at the tumor sites could be partially internalized by various cell components. 45 As a result, the red fluorescence signals in tumors could be attributed to the fluorescence dyes that were encapsulated in and released from the nanovehicles, which could be used to characterize their distribution profiles in tumor tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The intensified aerobic glycolysis of cancer cells-the Warburg effect-results in copious H + and the overproduction of lactate in tumor microenvironments 151,152 . This phenomenon initiates the local downregulation of extracellular pH in cancer cells, which is approximately 6.7-7.1 153 . Many anticancer drug delivery systems take advantage of the pH differences between healthy tissues (~7.4) and solid tumors (6.7-7.1).…”
Section: Response To Phmentioning
confidence: 99%
“…82 The aim of quantifying the distribution of nanoparticles inside/outside tumor cells was also demonstrated through a pH/light dual-response monochromatic ratiometric imaging nanoparticle (MRIN). 83 The fluorescence signal of MRIN remained in the ''OFF'' state, while the signal from Cy5 was switched ''ON'' as MRIN dissociated in the lysosome. The intracellular and extracellular Cy5 fluorescence signals were illuminated and the fluorescence signal from Cy5 of the extracellularly distributed nanoparticles was quantified via an 808 nm laser to photodegrade Cy7.5.…”
Section: Design Principles Of Nanoprobesmentioning
confidence: 99%